2020
DOI: 10.1161/jaha.119.013827
|View full text |Cite
|
Sign up to set email alerts
|

Association of Heart Rate Variability With Cognitive Performance: The Multi‐Ethnic Study of Atherosclerosis

Abstract: Background Heart rate variability ( HRV ) is associated with vascular risk factors for dementia, but whether HRV is associated with specific domains of cognitive performance is unclear. Methods and Results In the Multi‐Ethnic Study of Atherosclerosis (N=3018; mean age 59.3±9.2 years), we assessed the relationship of 10‐second HRV to scores on tests of global cognitive performance (Cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 53 publications
6
52
1
Order By: Relevance
“…In accordance with the present results, higher SDNN was cross‐sectionally associated with better performance of working memory [ 87 ]. Regarding cognitive performance, a study reported that HRV, especially SDNN, pNN50, and RMSSD were significantly higher in high-performance individuals during medium and high-level chess problems relative to their low-performance counterparts [ 62 ].…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with the present results, higher SDNN was cross‐sectionally associated with better performance of working memory [ 87 ]. Regarding cognitive performance, a study reported that HRV, especially SDNN, pNN50, and RMSSD were significantly higher in high-performance individuals during medium and high-level chess problems relative to their low-performance counterparts [ 62 ].…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, a recent review of non-psychiatric patients presented evidence that, under resting conditions, HF-HRV is associated with greater activity in brain regions involved in working memory, executive functioning, decision making and socially driven interactions, including the right dorsolateral PFC (DLPFC), right superior frontal cortex, and anterior cingulate cortex 74 . Moreover, HRV parameters have been positively correlated with performance on tests of global cognitive functioning, processing speed and working memory 75 , and reduced HRV has been independently associated with abnormal PFC activity 76 and reduced regional cerebral blood flow 77 in healthy individuals. While no studies to date have investigated HRV in relation to mental processes such as attention and working memory in SCZ, there have been studies focused on the role of autonomic function in social cognition (see Supplementary Table 2 ).…”
Section: Implications Of Autonomic Dysfunction In Sczmentioning
confidence: 99%
“…Structural brain lesions, including (clinically unrecognized) brain infarcts, white matter lesions and microbleeds have been reported to contribute to cognitive dysfunction in AF patients [6,7]. Cardiac autonomic function (CAF) has been related to cognitive performance in sinus rhythm (SR) patients [8][9][10][11][12][13]. CAF can be quantified by means of heart rate variability (HRV) derived from Holter ECG but also from standard ECG recordings [14].…”
Section: Introductionmentioning
confidence: 99%